OPTIMASI SISTEM LAYANAN ASISTEN RUMAH TANGGA BERBASIS MOBILE DENGAN EVALUASI TECHNOLOGY ACCEPTANCE MODEL - Daniawan, Benny; Culadi, Rafael Daniel; Hermawan, Aditiya; Ceng Giap, Yo (STMIK Sinar Nusantara, 2026)
In the contemporary era, individuals increasingly face demanding work schedules that often exceed standard working hours, intensifying challenges in balancing professional and domestic responsibilities. Household assistant services have emerged as a practical solution to support daily household activities. This study aims to design and evaluate a mobile-based household assistant service system that enables efficient interaction between service providers and employers, while enhancing accessibility, streamlining recruitment processes, and improving user experience through digital integration. To evaluate user acceptance, the study adopts the Technology Acceptance Model (TAM), focusing on Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Using (ATU), and Behavioral Intention to Use (BITU). Data were collected from 105 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that PEOU significantly influences PU (t = 11.324, p < 0.001), explaining 47.6% of its variance. Moreover, PEOU and PU jointly affect ATU (R² = 0.617), while ATU significantly influences BITU (R² = 0.495). However, PU does not directly affect BITU, indicating that perceived usefulness alone is insufficient to drive user intention without supportive attitudinal factors.